Students’ Mathematical Literacy Based on Self-Efficacy By Discovery Learning With Higher Order Thinking Skills-Oriented - Martalyna, Wihdati; Isnarto, Isnarto; Asikin, Mohammad (Universitas Negeri Semarang, 2018)
Purposes of this research are to describe the quality of Discovery Learning with higher order thinking skills-oriented to students’ mathematical literacy, to describe students’ mathematical literacy based on their self-efficacy, and to analyze the influence of self-efficacy towards students' mathematical literacy. This research uses mixed method by concurrent embedded design type. The subjects are the students of first grade of SMA Negeri 1 Slawi. Based on the three stages of learning quality, Discovery Learning with higher order thinking skills-oriented is qualified to student's mathematical literacy. In the case of aspect of the process of mathematical literacy, students with high self-efficacy are able to master the four aspects excellently, and they able to master the other three aspects well with some mistakes. Students with medium self-efficacy are mastering one aspect well, and cannot mastering the other six aspects well. Students with low self-efficacy cannot master five aspects maximally, and cannot master two other aspects. Mathematical literacy are influenced by self-efficacy about 34.6%.